Direcţii de acţiune pentru creşterea accesului la educaţie al copiilor provenind din medii defavorizate - Stoica, Laura (Calitatea Vieții, 2006)
This article presents the main conclusions and directions of intervention for the improvement of the educational situation of disadvantaged children. The most important aspects concern the limited access to education and the inequalities in educational chances that poor children are confronted with. The conclusions presented in this article were elaborated in the frame of the VIASAN project “The polarisation of the access to education and health as poverty source in the future” (coordinated by Prof. Ioan Mărginean) and conducted by RIQL, in the last two years. The article describes the existing strategies and national programs in the field of education and presents the solutions that the research team identified during the case study included in this project.